2018
DOI: 10.1155/2018/6171906
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Hexavalent Chromium by Diphenylcarbazide-GraftedMacadamiaNutshell Powder

Abstract: Macadamia nutshell powder oxidized by hydrogen peroxide solutions (MHP) was functionalized by immobilizing 1,5′-diphenylcarbazide (DPC) on its surface. The effectiveness of grafting was confirmed by the Fourier transform infrared spectrum due to the presence of NH and C=C stretches at 3361, 1591, and 1486 cm−1, respectively, on the grafted material which were absent in the nongrafted material. Thermogravimetric analysis revealed that the presence of DPC on the surface of Macadamia shells lowered the thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…The decrease in Cr(VI) adsorption capacity with increase in dosage is attributed to unsaturation of many active sites of the adsorbent during the adsorption process [28]. A similar trend was highlighted in the adsorption of Cr(VI) using diphenylcarbazide-grafted macadamia nutshell powder [29]. Fig.…”
Section: Influence Of Contact Time and Adsorbent Dosesupporting
confidence: 58%
“…The decrease in Cr(VI) adsorption capacity with increase in dosage is attributed to unsaturation of many active sites of the adsorbent during the adsorption process [28]. A similar trend was highlighted in the adsorption of Cr(VI) using diphenylcarbazide-grafted macadamia nutshell powder [29]. Fig.…”
Section: Influence Of Contact Time and Adsorbent Dosesupporting
confidence: 58%
“…These include biological treatment with bacteria or fungi, chemical treatment (or bleaching) with an alkaline solution, and oxidizing agents, physical treatment methods like mechanical agitation or sonication, and physicochemical methods such as steam explosion. 108 In addition to the above, cross-linking, graing, converting to activated carbon or fabricating biocomposites are usually the secondary treatments undertaken. 62,65,67,68,70,72 Recent literature has revealed that new or alternative adsorbents for the removal of Cr(VI) are experimented.…”
Section: àmentioning
confidence: 99%
“…Rodrigues et al also fabricated activated carbon from macadamia nutshell and used it as an adsorbent for the effective removal of organic solvents such as phenol [27]. The macadamia-based biochars were also successfully employed for the removal of toxic metal ions [28][29][30][31][32]. However, the application of macadamia nutshell-derived biochar solely for the removal of Zn 2+ and Cu 2+ seems to be scarce.…”
Section: Introductionmentioning
confidence: 99%